The association between experiencing homelessness in childhood or youth and adult housing stability in Housing First - Milad Parpouchi (BMC Psychiatry, 2021)
Abstract Background Researchers have pointed out the paucity of research investigating long-term consequences of experiencing homelessness in childhood or youth. Limited research has indicated that the experience of homelessness in childhood or youth is associated with adverse adjustment-related consequences in adulthood. Housing First (HF) has acknowledged effectiveness in improving housing outcomes among adults experiencing homelessness and living with serious mental illness, although some HF clients struggle with maintaining housing. The current study was conducted to examine whether the experience of homelessness in childhood or youth increases the odds of poorer housing stability following entry into high-fidelity HF among adults experiencing serious mental illness and who were formerly homeless. Methods Data were drawn from the active intervention arms of a HF randomized controlled trial in Metro Vancouver, Canada. Participants (n = 297) were referred to the study from service agencies serving adults experiencing homelessness and mental illness between October 2009 and June 2011. The Residential Time-Line Follow-Back Inventory was used to measure housing stability. Least absolute shrinkage and selection operator was used to estimate the association between first experiencing homelessness in childhood or youth and later housing stability as an adult in HF. Results Analyses indicated that homelessness in childhood or youth was negatively associated with experiencing housing stability as an adult in HF (aOR = 0.53; 95% CI = 0.31–0.90). Conclusions Further supports are needed within HF to increase housing stability among adult clients who have experienced homelessness in childhood or youth. Asking clients about the age they first experienced homelessness may be of clinical utility upon enrollment in HF and may help identify support needs related to developmental experiences. Results further emphasize the importance of intervening earlier in life in childhood and youth before experiencing homelessness or before it becomes chronic. Findings also contribute to a limited knowledge base regarding the adverse long-term consequences of childhood and youth homelessness. Trial registration Current Controlled Trials: ISRCTN57595077 and ISRCTN66721740 . Registered on October 9, 2012.